The effect of alcohol intoxication on haemodynamic physiology of acute cardiac tamponade - Hewitt, Peter MacDonald (Department of Surgery, 2017)
It is generally accepted that alcohol impairs haemodynamic physiology in normal subjects. Alcohol is also thought to have a detrimental effect in shock states. However, most research has concentrated on haemorrhagic shock, whereas in cardiac tamponade, the pathophysiology of shock is very different. Although some studies have mentioned alcohol as a negative factor in patients with cardiac tamponade, none have adequately assessed its effect. In a clinical study of 50 patients who presented to Groote Schuur Hospital Trauma Unit with acute cardiac tamponade due to penetrating chest injury, those who were intoxicated fared the same as their sober counterparts. Although more patients in the intoxicated group were "moribund" or "in extremis" on admission, this did not lead to a higher overall mortality. Haemodynamic parameters and results of special investigations in the two groups were also similar. These findings suggested that intoxicated patients with cardiogenic shock, specifically acute cardiac tamponade, behaved differently from intoxicated patients with haemorrhagic shock. However, the multitude of variables and the stress involved in treating patients with life-threatening acute conditions, makes studies such as this difficult. Because of these limitations, an animal model of acute cardiac tamponade was developed, so that actions of alcohol on haemodynamic physiology could be studied in a controlled environment. Fourteen young pigs were randomly assigned to receive either 30% alcohol or tap-water via a gastrostomy. The former resulted in blood alcohol levels which were compatible with moderate to severe intoxication. Cardiac tamponade was then induced by instilling warmed plasmalyte-8 into the pericardia! sac using a pressure-cycled system. Despite the fact that animals in the tamponade/alcohol group were more hypotensive, and reflex increase in heart rate was inhibited, cardiac output was similar in the two groups. The actions of alcohol in isolation were also studied in eight sham-operated pigs. The only noticeable effect in this instance were higher pulmonary artery wedge pressures in the sham/non-alcohol group. In other words, cardiac performance in both the tamponade/alcohol and sham/alcohol groups was at least equal to, or even better than that in animals that did not receive alcohol. It would seem therefore, that alcohol does not have a negative effect on haemodynamic physiology of acute cardiac tamponade. Theoretically, alcohol may "protect" patients with acute cardiac tamponade by decreasing peripheral vascular resistance and "afterload". It is also possible that inhibitory actions on the respiratory centre may prevent hyperpnoea or tachypnoea, and thereby diminish competitive filling of the right and left ventricles. However, further studies of cardiac function in intoxicated subjects with tamponade using more sophisticated techniques are necessary, before mechanisms will become apparent. In practice, an aggressive approach should be adopted towards moribund patients with penetrating chest injuries; if they have acute cardiac tamponade and are intoxicated, their prognosis is not necessarily dismal. This is of particular relevance in Cape Town, where both alcohol abuse and assault are endemic. As for a therapeutic effect of alcohol, these studies do not support its use for pharmacological manipulation of cardiac tamponade.